2014
DOI: 10.1371/journal.pone.0089899
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Hedgehog Acyltransferase-Catalyzed Sonic Hedgehog Palmitoylation Causes Reduced Signaling, Proliferation and Invasiveness of Human Carcinoma Cells

Abstract: Overexpression of Hedgehog family proteins contributes to the aetiology of many cancers. To be highly active, Hedgehog proteins must be palmitoylated at their N-terminus by the MBOAT family multispanning membrane enzyme Hedgehog acyltransferase (Hhat). In a pancreatic ductal adenocarcinoma (PDAC) cell line PANC-1 and transfected HEK293a cells Hhat localized to the endoplasmic reticulum. siRNA knockdown showed that Hhat is required for Sonic hedgehog (Shh) palmitoylation, for its assembly into high molecular we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 51 publications
(80 reference statements)
3
39
0
Order By: Relevance
“…The latter conclusion is supported by the detection of increased soluble product amounts from non-palmitoylated Shh C25A in comparison to palmitoylated protein products (compare relative amounts of soluble and cellular material produced in CHO-K1 tg cells; Fig. 2C,D, left lanes) and the findings of others (Chamoun et al, 2001;Konitsiotis et al, 2014).…”
Section: Loss Of Dally Function In Hh-producing Cells Affects Drosophsupporting
confidence: 55%
See 1 more Smart Citation
“…The latter conclusion is supported by the detection of increased soluble product amounts from non-palmitoylated Shh C25A in comparison to palmitoylated protein products (compare relative amounts of soluble and cellular material produced in CHO-K1 tg cells; Fig. 2C,D, left lanes) and the findings of others (Chamoun et al, 2001;Konitsiotis et al, 2014).…”
Section: Loss Of Dally Function In Hh-producing Cells Affects Drosophsupporting
confidence: 55%
“…2B, asterisk). These results demonstrate that both Hh lipidations contribute to Hh association with the cell membrane (Chamoun et al, 2001;Konitsiotis et al, 2014;Ohlig et al, 2011) to ensure that only fully processed Hh is released (Ohlig et al, 2012). This raises the question of how Hh shedding is controlled.…”
Section: Loss Of Dally Function In Hh-producing Cells Affects Drosophmentioning
confidence: 80%
“…Due to the palmitate amide linkage on Hh ligands, a product of S to N acyl migration from a cysteine side chain to the free amino terminus, Hh proteins do not undergo cycles of acylation and deacylation, a behavior similar to O-palmitoylated Wnt proteins [10 ,25]. Recently, it was shown that palmitoylation is important for sonic Hedgehog signaling and its role in proliferation and invasiveness of human carcinoma cells [26].…”
Section: N-terminal Acylation (N-palmitoylation)mentioning
confidence: 99%
“…• EW12/PERL tumour suppressor function [300] • Influence proliferation and invasiveness of human carcinoma [301] • Breast cancer cell migration [302] • Migration and adhesion of cancer cells [303] Resistance to virus and bacterial infection…”
Section: Metabolicmentioning
confidence: 99%